HISTORICAL PERFORMANCE OF THE SUBJECTS THE HUMAN BEING IN ITS ENVIRONMENT AND GLOBALIZATION AND ENVIRONMENT OF THE PERIOD 2007-2015 (Revista Electrónica Calidad en la Educación Superior, 2017)
AbstractThis article focuses on systematizing the historical enrollment lists of the students of the subjects Human Being in its Environment and Globalization and Environment between 2007 and 2015. The objective of the research is to know about student performance and the percentage of approval and failing per year, in these two subjects pertaining to the General Study Plan.  It was made a review of the grades, justified and unjustified withdrawals and no shows, among others, in order to show the students’ academic success; at the same time it was made a review of the academic orientations of all periods to account the number of evaluation instruments that are used in each quarter. As a general result it was identified that the average approval ranges from 68% to 70% and the average number of students that fail ranges between 23% and 20%; these data are related to the sum of summation activities used per term. As a conclusion, there is no direct relation with the number of instruments and the percentage of approved and failed students; In addition, the percentage of failures is considered acceptable because the majority of students were freshmen, which means these subjects were the first contact with a distance education system, different from the classroom system. It is recommended to apply tools to know the social situation of the students in order to improve academic performance; in addition, it is suggested to use the university experience with the use of digital tools   by implementing a pilot project in some university centers. Keywords: